Hannah Arendt - Martin Heidegger - Ettinger, Elżbieta (Yale Univ. Press, 1995)
This book is the first to tell in detail the story of the passionate and secret love affair between two of the most prominent philosophers of the twentieth century, Hannah Arendt and Martin Heidegger. Drawing on their previously unknown correspondence, Elzbieta Ettinger describes a relationship that lasted for more than half a century, a relationship that sheds startling light on both individuals, challenging our image of Heidegger as an austere and abstract thinker and of Arendt as a consummately independent and self-assured personality